Sheet, sealing material, fuel cell, electrolytic cell, method for producing sheet, and method for producing sealing material
By adding solvent to the modified mica to form a slurry drying, a clay sheet with excellent electrical insulation under high temperature environment was prepared, which solved the problem of insufficient electrical insulation at high temperatures in the existing expanded clay sheet, and achieved a sealing material with high insulation and high resilience.
Patent Information
- Application Number
- CN202380056654.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-27
- Publication Date
- 2025-03-11
AI Technical Summary
The existing expanded clay sheets are insufficient electrical insulation in high temperature environments and contain a large amount of iron components to cause conductivity, which limits their use near electronic components and electrodes.
By adding a solvent such as water to the modified mica to form a slurry drying, a sheet with excellent electrical insulation under a high temperature environment was prepared. The sheet is based on clay, with a content of more than 90%, and is modified by exchange ions to improve its stability.
High insulation in high temperature environments are achieved, iron composition is reduced, conductivity problems are avoided, and resilience and sealing are improved by adding filler materials.
Smart Images

Figure CN119605001A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sheet, a sealing material, a fuel cell, an electrolytic cell, a method for producing the sheet, and a method for producing the sealing material. Background Art
[0002] Sealing materials such as gaskets and packings are used in various industrial devices and pipe flanges. As gaskets, sheet-shaped gaskets, spiral-shaped gaskets, serrated gaskets, and the like are known.
[0003] In particular, a sheet containing clay as a main component is used for a sealing gasket for high temperature. Clay sheets are divided into sheets using non-expanding clay and sheets using expanding clay. Among them, in the conventional sheets using expanding clay or sealing materials using the sheets, materials obtained by modifying and expanding vermiculite (modified vermiculite) and the like are used as raw materials.
[0004] For example, Patent Document 1 describes a sheet containing modified vermiculite as expanded clay and a sealing material using the sheet. Patent Document 2 describes a sealing material using a sheet containing modified vermiculite as expanded clay.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: U.S. Patent No. 3325340
[0008] Patent Document 2: Japanese Patent No. 4745691
[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 58-9955
[0010] Patent Document 4: International Publication No. 2017 / 115399
[0011] Patent Document 5: Japanese Patent Application No. 2015-535911
[0012] Patent Document 6: Japanese Patent Publication No. 7-8724
[0013] Patent Document 7: Japanese Patent No. 6754746
[0014] Patent Document 8: Japanese Patent No. 3855003
[0015] Patent Document 9: Japanese Patent No. 3468747
[0016] Patent Document 10: Japanese Patent Application Publication No. 2007-254188
[0017] Patent Document 11: Japanese Patent Application Publication No. 2017-71512 Summary of the invention
[0018] Problems to be solved by the invention
[0019] When a conventional clay sheet using expanded clay is used as a sealing material, there are the following problems.
[0020] The modified vermiculite disclosed in Patent Documents 1 and 2 can be formed into sheets without using fibers and binders and has sealing properties in high temperature environments. However, since it contains a large amount of iron, it is conductive and has limitations when used near electronic components or electrodes that require insulation.
[0021] The present invention has been made in view of the fact that the existing clay sheets have insufficient electrical insulation properties in the above-mentioned high temperature environment. The purpose of the present invention is to provide a clay-based sheet with excellent electrical insulation properties in a high temperature environment, a sealing material, a fuel cell using the sealing material, an electrolytic cell, a sheet manufacturing method, and a sealing material manufacturing method.
[0022] Means for solving problems
[0023] The present inventors have conducted intensive studies and have found that a sheet having excellent electrical insulating properties in a high-temperature environment can be obtained by drying a slurry prepared by adding a solvent such as water to modified muscovite.
[0024] The present invention relates to the following sheets, sealing materials, fuel cells and electrolytic cells using the sealing materials, and methods for producing sheets and sealing materials.
[0025] [1] A sheet comprising a first component as a main component,
[0026] The first component is clay,
[0027] The diameter change rate as heating dimensional stability is less than 10%,
[0028] When the weight of the entire sheet is set to 100 weight %, the content of iron oxide is 6 weight % or less.
[0029] [2] The sheet according to [1] above, comprising a first component and optionally a second component,
[0030] The first component is expanded clay,
[0031] The second component is a filler.
[0032] When the weight of the entire sheet is set to 100 weight %, the total amount of the first component and the second component is 90 weight % or more.
[0033] The above-mentioned first component: the above-mentioned second component = 20:80 to 100:0.
[0034] [3] The sheet according to [1] above, wherein the first component is expanded muscovite.
[0035] [4] The sheet according to [1] above, wherein the content of aluminum oxide is 16% by weight or more when the weight of the entire sheet is 100% by weight.
[0036] [5] The sheet according to [1] or [2], wherein the expanded clay is expanded muscovite.
[0037] In the above expanded muscovite, K between the layers of muscovite + At least a portion of the ions are Li + Ion exchange.
[0038] [6] The sheet according to [2] above, wherein the second component is a filler of clay or oxide.
[0039] [7] The sheet according to [2] above, wherein the volume-based cumulative 50% particle size (D 50 ) is 5 to 50 μm.
[0040] [8] The sheet according to [1] or [2] above, wherein the content of the binder is 0.1% by weight or less.
[0041] [9] The sheet according to [1] or [2] above, wherein the content of iron oxide is 3 wt% or less when the weight of the entire sheet is taken as 100 wt%.
[0042]
[10] A sealing material comprising the sheet according to any one of [1] to [9] above.
[0043]
[11] The sealing material according to
[10] above, which is for use in a fuel cell or an electrolytic cell.
[0044]
[12] A fuel cell or an electrolytic cell comprising the sealing material described in
[11] above.
[0045]
[13] A method for producing a sheet, which is the method for producing a sheet according to any one of [1] to [9] above,
[0046] The method includes the step of mixing the first component and the second component to form a mixture.
[0047]
[14] A method for producing a sealing material, comprising the step of assembling a sheet produced by the method for producing a sheet according to
[13] as a part of a sealing gasket or a sealing packing.
[0048] Effects of the Invention
[0049] The sheet containing clay as the first component, such as expanded muscovite, has a lower iron content than the vermiculite-based and phlogopite-based sheets, and therefore has high insulation properties. In addition, since the sheet using clay such as expanded muscovite is not mixed with fibers or binders, it has high sealing properties and does not generate outgassing. Furthermore, by adding fillers, the resilience of the sheet is improved. Therefore, it is possible to achieve high heat resistance, high sealing properties, reduced outgassing, and control of resilience (high compression properties) that cannot be achieved in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The graph shows the particle size of muscovite used for modification, and the properties and sheet appearance after modification.
[0051] Figure 2 This is a table showing the second component used.
[0052] Figure 3 This is a table showing the sheets and sealing materials of Examples 1 to 5.
[0053] Figure 4 This is a table showing the sheets and sealing materials of Examples 6 to 10.
[0054] Figure 5 This is a table showing the sheets and sealing materials of Examples 11 to 14.
[0055] Figure 6 This is a table showing the sheets and sealing materials of Comparative Examples 1 to 4.
[0056] Figure 7 This is a table showing the results of volume resistivity measurement. DETAILED DESCRIPTION
[0057] Hereinafter, an embodiment of the present invention (hereinafter referred to as the present embodiment) will be described with reference to the drawings. The present embodiment relates to a sheet, a sealing material, a method for producing a sheet, and a method for producing a sealing material.
[0058] <Definition>
[0059] In the present specification, ○ to △ (for example, ○ weight % to △ weight %) means ○ or more and △ or less (○ weight % or more and △ weight % or less).
[0060] In addition, in the present specification, the terms “comprising” or “including” mean that the specified components are included, but do not exclude the presence of other components.
[0061] <film>
[0062] The sheet of the present embodiment can be used, for example, as a sealing material. The sheet of the present embodiment contains the first component as a main component and optionally contains a second component.
[0063] (1st ingredient)
[0064] The first component is expanded clay, preferably expanded muscovite. Here, "muscovite" is a concept including "sericite" which is another name when it is fine particles. In addition, expanded muscovite includes "expanded sericite" when it is fine particles. Expanded muscovite refers to K-rich clay located between the layers of muscovite. + At least a portion of the ions are selected from Li + Ions, Ca 2+ Ion, Mg 2+ A material that is exchanged with at least one ion (ion that imparts expansion properties) from a group of ions. Expanded sericite refers to K-rich mica located between the layers of sericite. + At least a portion of the ions are selected from Li + Ions, Ca 2+ Ion, Mg 2+ A material that exchanges at least one ion (ion imparting swelling property) from a group of ions.
[0065] Muscovite is a type of silicate mineral (layered silicate mineral), with the chemical formula K2Al4(Si6·Al2)O 20 (OH)4 represents a triple structure containing Al and K between layers of silicate tetrahedron. Sericite is fine particles of muscovite, which is a layered silicate mineral. As the muscovite used in this embodiment, it is preferably a fluorine-containing fluorine mica type muscovite from the viewpoint of preventing the generation of fluorine-based gases.
[0066] When the first component is preferably expanded muscovite, K + At least a portion of the ions are modified by Li + The modification of muscovite is not particularly limited, for example, muscovite or sericite can be mixed with heated molten lithium nitrate and reacted for a predetermined time. The dispersion of expanded muscovite in water can be carried out, for example, by removing lithium nitrate by filtration and washing, and then adding pure water and stirring.
[0067] Li contained in the interlayer of expanded muscovite + Ions and K + The ratio of ions is Li + :K +=20at%:80at%~70at%:30at%, preferably Li + :K + =30at%:70at%~60at%:40at%, more preferably Li + :K + =40at%:60at% to 60at%:40at%, more preferably Li + :K + =40at%:60at%~55at%:45at%. The exchanged ions are not K + But Ca 2+ Mg 2+ The same ratio applies to the case of .
[0068] When the weight of the whole sheet is set to 100% by weight, the first component comprises more than 90% by weight. In addition, when the total weight of the first component and the second component is set to 100% by weight, the first component at least comprises more than 25% by weight, preferably comprises more than 30% by weight, more preferably comprises more than 50% by weight, further preferably comprises more than 60% by weight, particularly preferably comprises more than 75% by weight, and particularly more preferably comprises more than 80% by weight. In addition, when the total weight of the first component and the second component is set to 100% by weight, the first component comprises less than 100% by weight, less than 90% by weight, less than 80% by weight, less than 70% by weight, less than 65% by weight, less than 50% by weight at most.
[0069] When the total weight of the first component and the second component is 100 weight%, the first component contains 25-100 weight%, 30-100 weight%, 40-100 weight%, 50-100 weight%, 60-100 weight%, 65-100 weight%, 70-100 weight%, 75-100 weight%, 80-100 weight%, 25-95 weight%, 25-90 weight%, 25-80 weight%, 25-75 weight%, 25-70 weight%, 25-65 weight%, 25-60 weight%, and 25-50 weight%.
[0070] The cumulative 50% particle size (D 50 ) is 5 to 500 μm, preferably 7 to 400 μm, more preferably 10 to 300 μm, further preferably 10 to 250 μm, and particularly preferably 10 to 230 μm.
[0071] (2nd ingredient)
[0072] The second component is a filler, preferably a filler of clay or oxide. The second component is optionally contained in the sheet. Here, the filler of clay or oxide refers to at least one selected from the group consisting of muscovite, sericite, talc, kaolinite, and fused silica. It should be noted that as these fillers, fired materials can also be used.
[0073] When the total weight of the first component and the second component is set to 100% by weight, the second component at least includes more than 10% by weight, preferably includes more than 20% by weight, more preferably includes more than 25% by weight, further preferably includes more than 30% by weight, particularly preferably includes more than 40% by weight, and particularly more preferably includes more than 50% by weight. In addition, when the total weight of the first component and the second component is set to 100% by weight, the second component includes less than 75% by weight, less than 70% by weight, less than 65% by weight, less than 60% by weight, less than 55% by weight, and less than 50% by weight at most. By changing the ratio of the second component, it is possible to adjust to an arbitrary state of resilience, but if excessively increased, the mechanical strength decreases.
[0074] When the total weight of the first component and the second component is 100 weight%, the second component contains 0-75 weight%, 0-70 weight%, 0-60 weight%, 0-50 weight%, 0-40 weight%, 0-35 weight%, 0-30 weight%, 0-25 weight%, 0-20 weight%, 5-75 weight%, 10-75 weight%, 20-75 weight%, 25-75 weight%, 30-75 weight%, 35-75 weight%, 40-75 weight%, and 50-75 weight%.
[0075] The volume-based cumulative 50% particle size (D 50 ) is 5 to 500 μm, preferably 7 to 400 μm, more preferably 10 to 300 μm, further preferably 10 to 250 μm, and particularly preferably 10 to 230 μm.
[0076] Taking the weight before heating as 100 weight %, the weight reduction rate of the second component when heated to 1000° C. is 15 weight % or less, preferably 13 weight % or less, more preferably 10 weight % or less, further preferably 8 weight % or less, further preferably 7 weight % or less, and particularly preferably 6 weight % or less.
[0077] The content of the iron component of the second component is small. Specifically, the content of the iron component converted into iron oxide (Fe2O3) contained in the second component is 3% by weight or less, preferably 2% by weight or less, more preferably 1.5% by weight or less, further preferably 1.0% by weight or less, and even more preferably 0.8% by weight or less, and particularly preferably 0.5% by weight or less. Here, the content of each component can be measured by fluorescent X-ray analysis (XRF) when expressed in terms of oxide conversion. It should be noted that even if the content of each component is expressed in terms of oxide conversion, each component does not necessarily need to be contained in the form of an oxide.
[0078] (Ratio of the total of the first component and the second component in the tablet)
[0079] When the weight of the entire sheet is set to 100 weight%, the total of the first component and the second component is 90 weight% or more, preferably 92 weight% or more, more preferably 93 weight% or more, further preferably 95 weight% or more, further more preferably 96 weight% or more, and particularly preferably 97 weight% or more.
[0080] (Content ratio of the first component to the second component)
[0081] The ratio of the content of the first component to the content of the second component (ratio by weight) is 10:90 to 100:0, 15:85 to 100:0, 20:80 to 100:0, 25:75 to 100:0, 30:70 to 100:0, 40:60 to 100:0, 50:50 to 100:0, 60:40 to 100:0, 65:35 to 100: 0, 70:30-100:0, 75:25-100:0, 80:20-100:0, 25:75-95:5, 25:75-90:10, 25:75-80:20, 25:75-75:25, 25:75-70:30, 25:75-65:35, 25:75-60:40, 25:75-50:50.
[0082] <Method for producing sheet>
[0083] The manufacturing method of the sheet of the present embodiment includes a step of mixing the first component and the second component to form a mixture. A solvent such as water is added to the mixture to adjust the slurry to a suitable viscosity that meets the molding method. Then, the mixture is molded using extrusion molding, a calender roll, a film applicator, a scraper, a rod coater, screen printing, etc., and dried to obtain a sheet.
[0084] <Sealing material>
[0085] The sheet of the present embodiment can be used for various industries, fuel cells such as high temperature fuel cells (SOFC), electrolytic cells such as solid oxide electrolytic cells (SOEC), and various piping sealing materials such as exhaust pipes of automobiles, such as sealing gaskets and sealing fillers. The sheet of the present embodiment can be used as a sealing material itself, or it can be used as a part of a sealing material such as a sealing gasket or a sealing filler. The shape of the product as a sealing material can be exemplified by a sheet-like sealing gasket, a spiral sealing gasket, a serrated sealing gasket, etc., but is not limited to these.
[0086] (Contains no adhesive)
[0087] The sheet of the present embodiment and the sealing material including the sheet do not substantially contain a binder. Here, the binder is not particularly limited, and examples thereof include rubber / adhesives, etc. More specifically, examples thereof include acrylonitrile butadiene rubber, styrene butadiene rubber, polybutadiene rubber, silicone rubber, acrylic rubber, natural rubber, butyl rubber, chloroprene rubber, ethylene propylene rubber, fluororubber, polyurethane rubber, acrylic adhesives, silicone adhesives, etc.
[0088] Substantially containing no binder means that, when the total weight of the sheet is 100 wt%, the content of the binder contained is less than 0.1 wt% (0.1 wt% or less), preferably less than 0.05 wt% (0.05 wt% or less), more preferably less than 0.01 wt% (0.01 wt% or less), further preferably less than 0.001 wt% (0.001 wt% or less), and particularly preferably less than 0.0001 wt% (0.0001 wt% or less). Since the sheet of the present embodiment is not mixed with a binder, it has high sealing properties when made into a sealing material and does not generate outgassing.
[0089] (Iron content)
[0090] The sheet of the present embodiment and the sealing material including the sheet have a low content of iron. Specifically, when the weight of the entire sheet is set to 100 weight%, the content of iron converted to iron oxide (Fe2O3) contained in the sheet of the present embodiment and the sealing material including the sheet is 6 weight% or less, preferably 3 weight% or less, more preferably 2 weight% or less, further preferably 1.5 weight% or less, further more preferably 1.0 weight% or less, and particularly preferably 0.8 weight% or less.
[0091] (Content of Alumina)
[0092] When the weight of the entire sheet is defined as 100 wt %, the content of aluminum oxide contained in the sheet of the present embodiment and the sealing material including the sheet is 16 wt % or more.
[0093] The sheet of this embodiment and the sealing material including the sheet have a lower iron content than the sheets using vermiculite and phlogopite, and therefore have high insulation properties. Therefore, they can be used for fuel cell applications such as solid oxide fuel cells (SOFC) and electrolytic cell applications such as solid oxide electrolytic cells (SOEC) that require high insulation properties.
[0094] (Basis Weight)
[0095] The basis weight of the sheet of the present embodiment and the sealing material including the sheet is preferably 700 to 1300 g / m 2 , more preferably 700 to 1200 g / m 2 , more preferably 750 to 1100 g / m 2 , particularly preferably 800 to 1050 g / m 2 .
[0096] (density)
[0097] The density of the sealing material of the present embodiment is preferably 0.5 to 2.5 g / cm at 2 MPa. 3 , more preferably 1.0 to 2.2 g / cm 3 , more preferably 1.2 to 2.0 g / cm 3 In this application, the density can be made to exceed 1.4g / cm 3 The lower the density at 2MPa, the easier it is to follow the unevenness of the target component during compression, and the less leakage from the contact surface.
[0098] The density of the sealing material of the present embodiment is preferably 0.5 to 2.8 g / cm at 20 MPa. 3 , more preferably 1.0 to 2.8 g / cm 3 , more preferably 1.2 to 2.8 g / cm 3 In this application, the density can be made to exceed 1.4g / cm 3 The higher the density at 20MPa, the denser it is when tightened, and the less physical leakage.
[0099] (Compression recovery)
[0100] The compression rate of the sealing material of this embodiment calculated by the method described in the examples is 15% or more, preferably 20% or more, more preferably 25% or more, further preferably 30% or more, and particularly preferably 40% or more. The higher the compression rate, the easier it is to follow the unevenness of the component as the object during compression, and the less leakage on the contact surface.
[0101] The sealing material of this embodiment has a recovery rate calculated by the method described in the examples of 5% or more, preferably 6% or more, more preferably 7% or more, further preferably 8% or more, and particularly preferably 10% or more. The higher the recovery rate, the greater the reaction force during tightening, and the less the contact surface leakage.
[0102] (Heating Dimensional Stability)
[0103] The sealing material of this embodiment has high heat resistance. Specifically, the diameter change rate calculated by the method described in the examples is 10% or less, preferably 8% or less, more preferably 5% or less, further preferably 3% or less, and particularly preferably 1% or less.
[0104] (Volume resistivity)
[0105] The sheet of the present embodiment and the sealing material including the sheet have excellent electrical insulation properties in a high temperature environment. Specifically, the sheet of the present embodiment and the sealing material including the sheet have a volume resistivity value calculated by the method described in the examples as insulation performance in a high temperature environment of more than 2.0×10 6 Ω·cm, and the volume resistivity is 3.8×10 6 Ω·cm or more.
[0106] (Fuel Cells and Electrolyzers)
[0107] The sealing material of the present embodiment has the above-mentioned characteristics, and therefore can be used as a fuel cell. That is, a fuel cell including the sealing material of the present embodiment can be provided. As a fuel cell, a flat-plate SOFC can be exemplified, but it is not limited thereto. In addition, as an electrolytic cell, a solid oxide electrolytic cell (SOEC) can be exemplified, but it is not limited thereto.
[0108] <Method for producing sealing material>
[0109] The method for producing a sealing material according to the present embodiment includes a step of assembling the sheet produced by the above-mentioned method for producing a sheet as a part of a sealing gasket and a sealing packing.
[0110] Example
[0111] Hereinafter, the present invention will be specifically described based on specific examples, but the present invention is not limited thereto.
[0112] <1. Production of expanded muscovite and production of sheets>
[0113] [1.1 Production of expanded muscovite (modification of muscovite)]
[0114] like Figure 1 As shown, five types of muscovite with different particle sizes are used. Lithium nitrate 8 times the weight of muscovite is melted at 370°C and mixed with muscovite. Ion exchange is performed by reacting at 370°C for 40 hours. Then, water is added and suction is performed. Wash with pure water and desalinate. Pure water is added and stirred to obtain a slurry.
[0115] [1.2 Production of Sheets]
[0116] The slurry obtained in the above [1.1] was concentrated, shaped using a doctor blade device, and dried at 100°C for 24 hours to produce a sheet. Figure 1 As shown in the appearance of the middle sheet, expanded muscovite (modified muscovite) was made from muscovite with different particle sizes, and as a result, all muscovite could be used for sheeting. The interlayer ions were investigated by fluorescent X-ray analysis (XRF). The results showed that the interlayer K + About 20 to 60 at% of the ions are exchanged for Li + ion( Figure 1 ).
[0117] As the first component, use Figure 1 LM7, LM11, LM20, LM42 shown.
[0118] As the second component, use Figure 2 Shown are muscovite before modification (M7 or 42), talc, kaolin, calcined muscovite (calcined M7), calcined kaolin (calcined kaolin), and fused silica.
[0119] The second component was added to the slurry of the first component obtained in [1.1] at a predetermined ratio and mixed to form a mixture. The obtained mixture was concentrated, shaped using a scraper device, and dried at 100° C. for 24 hours to produce sheets of Examples and Comparative Examples. The sheets of Comparative Examples 2 and 3 used expanded vermiculite instead of expanded muscovite as the first component.
[0120] Comparative Example 4 used a commercially available silicone-integrated phlogopite sheet.
[0121] <2. Film Evaluation>
[0122] The following evaluations were performed on the sheets of the examples and comparative examples. The results are shown in Figure 3 to Figure 5 .
[0123] (Compression recovery)
[0124] The sheet was punched out to prepare a test piece with an outer diameter of 20 mm, and the test piece was dried at 100° C. for 24 hours.
[0125] A compression fixture with three linear measuring instrument sensors installed at 120° intervals was set on a universal testing machine, and the test piece was placed in the center and a surface pressure of 0.16MPa was applied. The test force was applied at a compression rate of 0.1MPa per second until the maximum surface pressure was 20MPa. Then, the test force was released at the same speed and restored until it reached 0.16MPa.
[0126] The compression rate and recovery rate were calculated by the following formula based on the thickness at 2 MPa surface pressure (= thickness at 2 MPa), when the maximum surface pressure reached 20 MPa (= thickness at 20 MPa), and when the test was completed when the pressure reached 0.16 MPa again (= thickness when restored to 0.16 MPa).
[0127]
[0128] (Compression recovery (high surface pressure))
[0129] The maximum surface pressure was changed to 125 MPa from the evaluation of the low surface pressure. The same test was performed without changing other conditions. If cracks were observed in the sample after the test, it was recorded as "yes", and if no cracks were observed, it was recorded as "no".
[0130] (Heating Dimensional Stability)
[0131] Punch out the sheet and make a test piece with an outer diameter of 20 mm. After drying the test piece at 100°C for 24 hours, cool it naturally in a dryer and measure the diameter (= diameter after drying) using a projector. Then, heat it at 900°C in an electric muffle furnace for 24 hours (heating...200°C / h, natural cooling), and cool it naturally. Measure the diameter (= diameter after heating) using a projector. Measure the diameter change rate using the following formula.
[0132]
[0133] (Sealing)
[0134] The sheet was punched out to prepare a ring-shaped test piece having an outer diameter of 92 mm and an inner diameter of 49 mm. The ring-shaped test piece was subjected to standard condition treatment at 24° C. and 50% RH for 24 hours.
[0135] The leakage rate is measured in accordance with standard EN13555 under the following test conditions.
[0136] Testing machine: AMTEC temes fl.ai1
[0137] Gas type: He
[0138] Internal pressure: 0.5MPa
[0139] Surface pressure: 20MPa
[0140] Detector: Leak detector
[0141] (TG)
[0142] The second component was ground in a mortar. Using a TG-DTA apparatus manufactured by RIGAKU, the heating weight loss at each temperature was measured under the following conditions.
[0143] Atmosphere: Air
[0144] Sample weight: 10 mg
[0145] Heating rate: 5℃ / min
[0146] Maximum temperature: 1000℃
[0147] Disc material: Pt
[0148] (Volume resistivity measurement)
[0149] The volume resistivity was measured with reference to Japanese Industrial Standards JIS C2141, JEC-6148, and JIS C2139, and was performed under the following test conditions.
[0150] Temperature 600℃
[0151] ·Atmosphere
[0152] ·Measurement method
[0153] The main electrode, protective electrode and counter electrode were printed on the upper and lower surfaces of the sample using a screen printer and silver paste, and then dried (in the atmosphere, 150°C, 12 hours), and then baked in an electric furnace (in the atmosphere, 700°C, 1 hour, heating rate 200°C / h) to form each electrode.
[0154] After maintaining at 600°C for 15 minutes, a DC voltage (V) was applied to the sample, and the current (I) after charging for 1 minute was measured to determine the volume resistance (Rv) of the sample. The volume resistivity (ρv) was calculated from the thickness (t) and electrode area (S) of the sample using the following formula.
[0155] If the thickness of the sample is t (cm), the volume resistivity ρv is given by the following formula.
[0156]
[0157] ρ v :Volume resistivity (Ω·cm)
[0158] t: thickness of the sample (cm)
[0159] S: Electrode effective area (cm 2 )
[0160] R v :Volume resistance(Ω)
[0161] g: electrode gap distance (cm)
[0162] D1 Main electrode diameter (cm)
[0163] D z : Diameter of the protective electrode (cm)
[0164] (result)
[0165] according to Figure 3 to Figure 7 The results shown confirmed the following results.
[0166] In the sheet of the example, the first component (expanded muscovite) and the second component (filler) are the main components, and no resin such as fluorine or a binder is contained, so the generation of outgassing is small.
[0167] The sheet of the example has high insulation properties because the iron content is as low as 2.1 wt % or less. Specifically, the volume resistivity of the sheet of the example is 3.8×10 6 Ω·cm or more, and excellent insulation performance in high temperature environments. Therefore, it can be used in fuel cells and electrolytic cells that require high insulation properties.
[0168] Regarding the heating dimensional stability of the sheets of Examples, it was found that no significant shrinkage was observed even when heated at 900° C., and that the sheets had sufficient heat resistance for high-temperature applications.
[0169] It is understood that the sheet of the example has high heat resistance because the clay phase remains even when heated at 900°C.
[0170] When a fired filler is used as the second component, it is expected that the weight loss during heating will be reduced, so that the heat resistance will be improved.
[0171] Since the sheet of Comparative Example 1 could not be flaked (could not be processed), it was found that the sheet could be flaked by modifying the muscovite mica.
[0172] As an effect brought about by the addition of the second component (filler), it was confirmed that the initial thickness (density) can be controlled and the amount of compression can be adjusted.
[0173] The evaluation results of the compression recovery (125 MPa) of the sheets of the examples showed that no fracture behavior was observed even when a high surface pressure was applied, and that the sheets had sufficient strength when used as sealing materials.
[0174] It can be seen that the compressed density of the sheet of the embodiment is high (the density at 20 MPa is 2.1 to 2.5 g / cm3 ), can be made into sealing materials with less physical leakage.
[0175] According to the sealing test results, the sheets of the examples have sufficient sealing properties when made into sealing materials.
[0176] On the other hand, the tablets of the comparative examples had a large content of the iron component (Comparative Examples 2 to 4).
[0177] It should be noted that the following prior arts and topics were also referred to in the creation of the present invention, and are not essential elements of the present invention, but can be appropriately introduced as needed.
[0178] In conventional sheets using non-expandable clay or sealing materials using the sheets, organic or inorganic fibers and a binder are added.
[0179] Patent Document 3 describes a sealing material containing mica as non-expanding clay, mixed with organic fibers and a binder. Patent Documents 4 and 5 describe a sealing material containing talc as non-expanding clay, mixed with inorganic fibers and a binder. Patent Document 6 describes a sheet containing tetrasilicon fluoride mica as expanding clay. Patent Document 7 describes a sealing material using a sheet containing tetrasilicon fluoride mica as expanding clay.
[0180] The sealing materials including non-expanding clay, fibers and binders shown in Patent Documents 3 to 5 have insufficient sealing properties because they contain fibers. In addition, when using organic binders and organic fibers, the organic components burn out in a high-temperature environment to produce gaps, and the sealing properties deteriorate. In addition, silicone is sometimes used as an inorganic binder, but it produces siloxane-based exhaust in a high-temperature environment and cannot be used near electronic components or electrodes. The fluorine mica shown in Patent Documents 6 and 7 can be flaked without the use of fibers and binders, and has sealing properties in a high-temperature environment. However, it is possible that a trace amount of fluorine-based gas will be produced in a high-temperature environment, and there are restrictions on its use near electronic components and electrodes.
[0181] Patent Document 8 describes a sheet containing montmorillonite, a type of smectite, as expanded clay, and a sealing material using the sheet. Patent Documents 9 to 11 describe that clay can be modified by reaction with a molten salt, a concentrated aqueous solution, or the like.
[0182] The montmorillonite shown in Patent Document 8 can be formed into sheets without using fibers or binders. However, it warps and shrinks significantly in high temperature environments, and has problems with dimensional stability. In addition, during manufacturing, since it gels at a relatively low concentration, it is easy to warp when drying, and there are problems with the formability of thick films. Patent Documents 9 to 11 record that clay can be modified by reaction with molten salts, concentrated aqueous solutions, etc. However, the technologies in these documents are limited in their use in the preparation of clay dispersions, composites with polymers, and mixing with resins.
Claims
1. A sheet comprising a first component as a main component, The first component is clay, The diameter change rate as heating dimensional stability is less than 10%, When the weight of the entire sheet is set to 100 weight %, the content of iron oxide is 6 weight % or less.
2. The sheet according to claim 1, comprising a first component and optionally a second component, The first component is expanded clay, The second component is a filler material, When the weight of the entire sheet is set to 100 weight %, the total amount of the first component and the second component is 90 weight % or more, The first component: the second component = 20:80 to 100:
0.
3. The sheet according to claim 1, wherein The first component is expanded muscovite.
4. The sheet according to claim 1, wherein When the weight of the entire sheet is set to 100 weight %, the content of aluminum oxide is 16 weight % or more.
5. The sheet according to claim 1 or 2, wherein: The expanded clay is expanded muscovite, In the expanded muscovite, K between the layers of muscovite + At least a portion of the ions are Li + Ion exchange.
6. The sheet according to claim 2, wherein The second component is a filler of clay or oxide.
7. The sheet according to claim 2, wherein The volume-based cumulative 50% particle size D of the second component measured by a laser diffraction / scattering particle size distribution analyzer is: 50 5μm~50μm.
8. The sheet according to claim 1 or 2, wherein: The content of the binder is 0.1 wt % or less.
9. The sheet according to claim 1 or 2, wherein: When the weight of the entire sheet is set to 100 weight %, the content of iron oxide is 3 weight % or less. 10 . A sealing material comprising the sheet according to claim 1 .
11. The sealing material according to claim 10, which is used in a fuel cell or an electrolytic cell.
12. A fuel cell or an electrolytic cell comprising the sealing material according to claim 11.
13. A method for producing a sheet, which is the method for producing a sheet according to any one of claims 1 to 9, The method includes the step of mixing the first component and the second component to form a mixture. 14 . A method for producing a sealing material, comprising the step of assembling the sheet produced by the method for producing a sheet according to claim 13 as a part of a sealing gasket or a sealing packing.
Citation Information
Patent Citations
Nickel alloy containing large quantity of chromium and element for centrifugal spinning machine
JP1983009955A
Mica sheet and its manufacturing method
JP1995008724B2
Method for producing acid-expandable mica
JP2007254188A
spiral gasket
JP2015535911A
Manufacturing method of water swellable layering silicate
JP2017071512A